A phenomenological and quantitative model for shape/temperature memory effect in polypyrrole undergoing relaxation transition. Issue 2 (2nd March 2015) - Lu, haibao; Yao, Yongtao; Lin, Long
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to present a phenomenological and quantitative model to study the constitutive relations and working mechanism for shape/temperature memory effect in polypyrrole (PPy)-based shape memory polymers (SMPs). Design/methodology/approach – In this paper, the origin of relaxation law was used to theoretically predict the relationships between relaxation time and internal energy and temperature based on the thermodynamics of polymers. Findings – A phenomenological model was proposed to quantitatively identify the factors that influence the stored mechanical energy, shape memory effect (SME) and temperature memory effect (TME) in PPy. Both structural relaxation law and Tool-Narayanaswamy (TN) model were used to couple the constitutive relations of stress and transition temperature as a function of relaxation frequency, respectively. Furthermore, the simulation of the phenomenological model was compared with experimental results reported in relevant literature for purpose of verification. Research limitations/implications – Exploration of the working mechanism underpinning the experimental (or phenomenal) results and significant enhancement of the understanding of relevant experimental features reported previously. Originality/value – The outcome of this study will provide a powerful phenomenological and quantitative tool for studies on SME and TME in SMPs.